2017
DOI: 10.3390/su9101746
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Structural Conditions and Cultural Inertia on Water Usage and Landscape Decision-Making in a California Metropolitan Area

Abstract: Urban development and planning are increasingly centered on matters of sustainability, balancing economic development with ecosystem services and biological diversity within urban environments. In addition to these institutional and structural factors, the decision-making process within individual households must be understood to address rising concerns about water use. Therefore, individual characteristics and preferences that influence the use of water also warrant examination. In response to a survey of occ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, these differences were not significantly reflected in the aesthetic value that was in general maintained for the other plant species studied in Phase 1 of the experiments (further detailed in [23]). This result indicates that it is possible to use those native species under deficit irrigation without losing the expected aesthetic value, which is an interesting plant feature considering that the end-users' preferences more frequently privilege aesthetics, regarding other aspects (e.g., environmental concerns) [19][20][21].…”
Section: Use Of Structural Materials With Water Retention Capacitymentioning
confidence: 92%
See 1 more Smart Citation
“…However, these differences were not significantly reflected in the aesthetic value that was in general maintained for the other plant species studied in Phase 1 of the experiments (further detailed in [23]). This result indicates that it is possible to use those native species under deficit irrigation without losing the expected aesthetic value, which is an interesting plant feature considering that the end-users' preferences more frequently privilege aesthetics, regarding other aspects (e.g., environmental concerns) [19][20][21].…”
Section: Use Of Structural Materials With Water Retention Capacitymentioning
confidence: 92%
“…Therefore, green roofs can be built as: i) aesthetically appealing environments; ii) ecosystem services providers; and iii) both, if environmental conditions allow to retain the aesthetic value. But aesthetics is a major driver of preference behaviour [19][20][21] and possibly only part of the end-users of green roofs in climates with hot and dry summers accept that sometimes there is a trade-off between aesthetics and ecosystem benefits, as less agreeable environments can provide relevant services.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Hensley et al found that Fresno showed stronger filtering effects on the avifauna with the urban bird assemblage showing lower similarity with the regional species pool compared to Tucson or Phoenix. This may be driven by differences in urban water use policies resulting in greater extent of lawns causing Fresno to diverge from the more arid natural surroundings (Katti et al, 2017); Tucson (and to a lesser extent, Phoenix) on the other hand has stronger water conservation measures resulting in more xeriscaped yards, reducing the contrast with the desert habitats of the larger landscape matrix around that city. These findings highlight a role for more intentional careful landscape design and planning in modulating the filtering effect of urbanization on regional biodiversity.…”
Section: The Challenge Of Biodiversity Conservation In the Anthropocenementioning
confidence: 99%
“…The study revealed that investment in the advanced design of façades could significantly increase electricity production and ensure sustainability in HRRBs. Recently, focusing on promoting and implementing sustainable water use practices in HRBs, Katti et al (2017) explored the influence of the interaction among social-structural, institutional and cultural factors on individual water use behaviours and landscape decision-making. The study focused on educating property marketers on how luxury is perceived to satisfy buyers effectively.…”
Section: Introductionmentioning
confidence: 99%